Current perspectives on defining and mitigating frailty in relation to critical illness. Issue 11 (November 2021) - Costa, N.A.; Minicucci, M.F.; Pereira, A.G.; de Paiva, S.A.R.; Okoshi, M.P.; Polegato, B.F.; Zornoff, L.A.M.; Villas Boas, P.J.F.; Atherton, P.J.; Phillips, B.E.; Banerjee, J.; Gordon, A.L.; et al.
Summary: Up to half of ICU survivors, many of whom were premorbidly well, will have residual functional and/or cognitive impairment and be vulnerable to future health problems. Frailty describes vulnerability to poor resolution of homeostasis after a stressor event but it is not clear whether the vulnerability seen after ICU correlates with clinical measures of frailty. In clinical practice, the scales most commonly used in critically ill patients are based on the assessment of severity and survival. Identification and monitoring of frailty in the ICU may be an alternative or complimentary approach, particularly if it helps explain vulnerability during the recovery and rehabilitation period. The purpose of this review is to discuss the use of tools to assess frailty status in the critically ill, and consider their importance in clinical practice. Amongst these, we consider biomarkers with potential to identify patients at greater or lesser risk of developing post-ICU vulnerability.